A polycarbonate gel electrolyte and its application

By using electrospinning PAN porous fiber membranes to form an interpenetrating crosslinking network structure with polycarbonate polymers in lithium batteries, the problem of flammability and explosion of lithium batteries at high temperatures is solved, and the electrochemical window, mechanical properties and high temperature resistance of electrolytes are improved. It is suitable for high energy density lithium battery applications.

CN116130756BActive Publication Date: 2025-04-01GUIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211568182.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2025-04-01
Estimated Expiration
2042-12-08

AI Technical Summary

Technical Problem

Existing lithium batteries are prone to combust and explosion at high temperatures, and their energy density is not enough to meet the long-term operation needs of large equipment. The safety and mechanical properties of traditional liquid electrolytes are also insufficient.

Method used

Electrospinning PAN porous fiber membrane is used as the substrate, and the polymerization of polycarbonate monomer, multifunctional thiol monomer, thermal initiator and electrolyte is carried out after heat-induced polymerization, forming a polycarbonate gel electrolyte.

Benefits of technology

It significantly improves the electrochemical window, mechanical properties and electrochemical performance stability of the electrolyte, enhances the resistance to dendrite growth, flame retardant and high temperature resistance, and is suitable for lithium battery applications in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116130756B_ABST
    Figure CN116130756B_ABST
Patent Text Reader

Abstract

The present invention discloses a polycarbonate gel electrolyte and its application. The electrolyte is prepared by thermally initiating polymerization after being soaked in a mixed solution of a polymerizable carbonate monomer, a multifunctional mercapto monomer, a thermal initiator and an electrolyte using an electrospun PAN porous fiber membrane as a substrate. The electrolyte is widely used in lithium metal batteries and has the characteristics of high electrochemical window, good mechanical properties, stable electrochemical properties, high resistance to dendrite growth, good flame retardancy and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a gel electrolyte and application thereof, in particular to a polycarbonate gel electrolyte and application thereof in a battery. Background Art

[0002] Lithium batteries have the advantages of high energy density, high electrochemical window, fast charge and discharge, and low self-discharge. They are one of the most widely used energy storage devices and have great application value in the field of electrochemical energy storage. However, commercial lithium batteries are prone to combustion and explosion at high temperatures, and the current energy density of lithium batteries can no longer meet the long-term operation of current large-scale equipment. Therefore, the development of lithium battery energy storage devices with high temperature resistance and high energy density will become the focus of the next stage of new energy research.

[0003] Electrolyte materials are one of the key factors affecting the performance of lithium batteries. Traditional lithium batteries use liquid electrolytes with organic small molecule carbonates as solvents. The advantages are good lithium salt solubility and high ion conductivity, but they are extremely flammable and explosive. How to synthesize electrolyte materials that are non-flammable, high temperature resistant and have excellent electrochemical properties through controllable preparation methods remains a challenge.

[0004] In recent years, gel polymer electrolyte materials have attracted much attention in energy storage fields such as lithium batteries, sodium batteries, and supercapacitors. Gel polymer electrolyte (GPE), as an intermediate state between liquid electrolytes and all-solid polymer electrolytes, is essentially a form of solid-liquid combination. Compared with liquid electrolytes and all-solid electrolytes, it has many advantages: (1) Gel polymer electrolytes have better safety performance, are non-flammable, and non-explosive; (2) The polymer structure is controllable, has good flexibility, and has good compatibility with the electrode interface; (3) It has high ionic conductivity and excellent electrochemical properties.

[0005] Although gel electrolytes have many advantages over traditional liquid electrolytes, they still have some shortcomings: (1) Due to polymer structure and material limitations, current gel polymer electrolytes cannot be used normally at extreme temperatures (150°C); (2) Since liquid electrolytes still exist in gel polymer electrolytes, their mechanical properties are not high and their electrochemical stability is poor, making it difficult to meet the requirements of assembly and high-intensity use; (3) Since traditional polymer substrates mostly use polyether (EO) structures with relatively low electrochemical windows, the application of high-energy-density positive electrode materials in lithium batteries is limited.

[0006] In summary, how to further improve the electrochemical window and mechanical properties of gel polymers, and at the same time, further improve the flame retardancy and high temperature resistance of electrolytes, is the key research direction of practitioners. Summary of the invention

[0007] The purpose of the present invention is to provide a polycarbonate gel electrolyte and its application. The polycarbonate gel electrolyte of the present invention has the characteristics of high electrochemical window, good mechanical properties, stable electrochemical properties, high resistance to dendrite growth, good flame retardancy and high temperature resistance.

[0008] The technical solution of the present invention is a polycarbonate gel electrolyte, which is prepared by thermally initiating polymerization after taking an electrospun PAN porous fiber membrane as a substrate and impregnating a mixed solution of a polymerizable carbonate monomer, a multifunctional mercapto monomer, a thermal initiator and an electrolyte.

[0009] The aforementioned polycarbonate gel electrolyte, the electrospun PAN porous fiber membrane has a fiber diameter of 350-450 nm and a thickness of 20-200 μm.

[0010] The aforementioned polycarbonate gel electrolyte, the general structural formula of the polymerizable carbonate monomer is as follows:

[0011]

[0012] In the aforementioned polycarbonate gel electrolyte, the functionality of the multifunctional mercapto monomer is greater than 2.

[0013] In the aforementioned polycarbonate gel electrolyte, the thermal initiator is azobisisobutyronitrile.

[0014] The aforementioned polycarbonate gel electrolyte, wherein the electrolyte is one of 1M LiDFOB in EC / DMC=1 / 1Vol%, 1M LiTFSI in EC / DMC=1 / 1Vol%, 1M LiTFSI in EC / DEC / DMC=1 / 1 / 1Vol%, and 1M LiDFOB inEC / DEC / DMC=1 / 1 / 1Vol%.

[0015] The aforementioned polycarbonate gel electrolyte, in the mixed solution, the molar ratio of the polymerizable carbonate monomer to the mercapto group-containing monomer is 1:1, the mass ratio of the mass of the electrolyte to the total mass of the polymerizable carbonate monomer and the mercapto group-containing monomer is 1:1; the amount of the thermal initiator used is 1% of the mass of the polymerizable carbonate monomer.

[0016] The aforementioned polycarbonate gel electrolyte, the thermally initiated polymerization is carried out by keeping the temperature at 75-85° C. for 3-5 hours.

[0017] An application of the aforementioned polycarbonate gel electrolyte in a lithium metal battery.

[0018] The aforementioned polycarbonate gel electrolyte is used in a battery by assembling the electrospun PAN porous fiber membrane soaked in the mixed solution with other components of the battery and then performing in-situ thermal polymerization.

[0019] The aforementioned application of the polycarbonate gel electrolyte in a battery, wherein the other components of the battery include a negative electrode shell, a spring sheet, a stainless steel sheet, a negative electrode, a positive electrode and a positive electrode shell, and the assembly order is the negative electrode shell, the spring sheet, the stainless steel sheet, the negative electrode, the electrospun PAN porous fiber membrane soaked in the mixed solution, the positive electrode and the positive electrode shell.

[0020] Beneficial Effects of the Invention

[0021] 1. The gel electrolyte of the present invention is based on an electrospun PAN porous fiber membrane, which is formed by thermally initiating polymerization after being impregnated with a mixed solution of a polymerizable carbonate monomer, a multifunctional thiol monomer, a thermal initiator and an electrolyte. The addition of carbonate groups significantly increases the oxidation potential of the electrolyte, making it have a very high electrochemical window (>5.2V).

[0022] 2. The present invention forms an interpenetrating cross-linked network structure through electrospinning PAN porous fiber membrane and polycarbonate polymer, which greatly improves the mechanical properties of the gel electrolyte; at the same time, polycarbonate is formed by in-situ polymerization in the three-dimensional network gap of the nanofibrous PAN structure, which greatly improves the flatness and uniformity of the gel electrolyte surface.

[0023] 3. The present invention forms a cross-linked network structure by in-situ polymerization of polymerizable carbonate monomers with multifunctional mercapto monomers in the three-dimensional network gaps of the nanofibrous PAN structure, which greatly increases the interfacial contact area between the gel electrolyte and the electrode, is beneficial to inhibiting the growth of lithium dendrites, and has the advantage of a higher degree of resistance to dendrite growth.

[0024] 4. The present invention uses carbonate polymer with good high temperature resistance and electrospun PAN porous fiber membrane as the substrate of the electrolyte, which can greatly improve the flame retardancy and high temperature resistance of the gel electrolyte.

[0025] 5. When the gel electrolyte of the present invention is applied to lithium metal batteries, the electrolyte raw materials are assembled into batteries and then in-situ polymerized, thereby further improving the compatibility between the electrolyte and the electrode sheet, and achieving a better effect in inhibiting dendrite growth.

[0026] In summary, the present invention has the advantages of high electrochemical window, good mechanical properties, stable electrochemical properties, high resistance to dendrite growth, and good flame retardancy and high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a flow chart of the preparation of the gel electrolyte.

[0028] Figure 2 This is a SEM image of the electrospun PAN fiber membrane prepared in Example 1 of the present invention.

[0029] Figure 3 This is the infrared spectrum of the cross-linked network structure of polycarbonate obtained in Example 2 of the present invention

[0030] Figure 4 Thermal stability properties (TG, DSC) of the electrospun PAN fiber membrane and polycarbonate cross-linked network structure prepared in Examples 1 and 2 of the present invention.

[0031] Figure 5 This is a stress-strain curve of the high-temperature and high-pressure electrospun PAN-based polycarbonate gel electrolyte prepared in Example 3 of the present invention.

[0032] Figure 6 This is the electrochemical window diagram of the high-temperature and high-pressure electrospun PAN-based polycarbonate gel electrolyte prepared in Example 3 of the present invention.

[0033] Figure 7 This is a test curve of the lithium symmetric battery cycle stability of the high-temperature and high-pressure electrospun PAN-based polycarbonate gel electrolyte prepared in Example 3 of the present invention.

[0034] Figure 8 This is a full battery cycle stability test curve of the high-temperature and high-pressure electrospun PAN-based polycarbonate gel electrolyte prepared in Example 3 of the present invention.

[0035] pass Figure 2 It can be seen that the electrospun PAN porous fiber membrane prepared by the process of Example 1 of the present invention has a fiber diameter of 400 nm and a thickness of 100 μm, and there are a large number of void structures between the fibers.

[0036] pass Figure 3 It can be seen that the infrared spectrum of the cross-linked network structure of polycarbonate obtained by the process of Example 2 of the present invention and the stretching vibration peaks are consistent with those reported in the literature, indicating that the cross-linked network of polycarbonate is successfully polymerized.

[0037] pass Figure 4 It can be seen that the polycarbonate cross-linked network structure (PTT) obtained by the process of Example 2 of the present invention has excellent thermal stability, wherein the temperatures at which the PTT weight loss reaches 5% and 10% are 310°C and 320°C, respectively, indicating that the polymer has a wide range of thermal stability suitable for high-temperature (150°C) lithium batteries.

[0038] pass Figure 5 It can be seen that the material of the high-temperature and high-pressure electrospun PAN-based polycarbonate gel electrolyte (PTTL-GPE) prepared by the process of Example 3 of the present invention has excellent mechanical properties, wherein the tensile strength of PTTL-GPE is 17.12 MPa, and the tensile strength of most gel electrolytes reported in the literature is at the KPa level.

[0039] pass Figure 6 It can be seen that the electrochemically stable voltage window diagram of the high-temperature and high-pressure electrospun PAN-based polycarbonate gel electrolyte prepared by the process of Example 3 of the present invention has a very high voltage window (5.2V), which is greater than 5.0V of PAN-LE, while the voltage window of the traditional liquid electrolyte is less than 5V (EC (4.8V) ≈ PC (4.8V) > EMC (4.6V)), wherein PAN-LE is an electrolyte in which the PAN fiber membrane directly loads the lithium electrolyte.

[0040] pass Figure 7 It can be seen that the lithium symmetric battery assembled with the high-temperature and high-pressure electrospun PAN-based polycarbonate gel electrolyte material prepared by the process of Example 3 of the present invention exhibits excellent electrochemical stability; before 600 hours of cycling, the overpotential remains basically unchanged (about 100 mV), and it has excellent lithium metal compatibility and lithium dendrite inhibition performance. Its excellent anti-dendrite performance may be attributed to the formation of Li3N by N on PAN and metallic lithium, which can provide a more stable interface between the electrolyte and Li metal.

[0041] pass Figure 8 It can be seen that the lithium metal full battery assembled with the high-temperature and high-pressure electrospun PAN-based polycarbonate gel electrolyte material prepared by the process of Example 3 of the present invention exhibits excellent charge and discharge stability. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with the embodiments, but they are not intended to limit the present invention.

[0043] Embodiments of the present invention

[0044] Example 1

[0045] First, PAN powder was dried in a vacuum oven at 80°C for 12 hours until the mass no longer changed. 1g of polyacrylonitrile (PAN) powder was dissolved in 9g of N,N-dimethylformamide (DMF) (concentration of 10wt%), heated (50°C), and stirred (6h) until a homogeneous solution was obtained to obtain PAN spinning solution. After standing for a period of time to eliminate the bubbles in the spinning solution, 10mL of the solution was drawn with a 10mL syringe and fixed on the spinning support. The spinning parameters were set as follows: spinning positive voltage 15kV, negative voltage 1kV, distance from needle to receiving roller 15cm, spinning injection rate 0.6mL / h, and a No. 21 needle. After spinning for 12 hours, a PAN fiber membrane was obtained and dried in a vacuum oven at 80°C for 12 hours so that the unvolatile DMF on the PAN fiber could be completely removed.

[0046] Example 2

[0047] 0.3g polymerizable carbonate monomer (TGAB), 0.25g trithiol monomer (TPTMP), 0.003g thermal initiator (azobisisobutyronitrile, AIBN, 1wt%) were mixed and stirred for 30min until a homogeneous solution was obtained to obtain a precursor solution (TT). Then, under a nitrogen environment, a thiol-ene click reaction was thermally initiated at 80°C to obtain a polycarbonate cross-linked network structure (TT).

[0048] 0.3 g of polymerizable carbonate monomer (TGAB), 0.25 g of trithiol monomer (TPTMP), and 0.003 g of thermal initiator (azobisisobutyronitrile, AIBN, 1 wt%) were mixed and stirred for 30 min until a homogeneous solution was obtained to obtain a precursor solution (TT); the precursor solution was impregnated on the PAN fiber membrane of Example 1, and then under a nitrogen environment, a thiol-ene click reaction was thermally initiated at 80°C to obtain a polycarbonate cross-linked network structure (PTT) of the PAN fiber membrane.

[0049] Example 3

[0050] 0.3g polymerizable carbonate monomer (TGAB), 0.25g trithiol monomer (TPTMP), 0.003g thermal initiator (azobisisobutyronitrile, AIBN, 1wt%), 0.55g electrolyte (LE, 1M LiDFOB in EC / DMC=1 / 1Vol%) were mixed and stirred for 30min until a homogeneous solution was obtained to obtain a precursor solution (TTL). Move to a glove box filled with argon (atmosphere: H2O, O2<0.1ppm) to complete the following operations: PAN was infiltrated with the precursor solution in the order of TTL precursor solution (15μL), PAN, and TTL precursor solution (15μL), and then thermally initiated to polymerize at 80℃ to obtain a high temperature and high pressure electrospun PAN-based polycarbonate gel electrolyte (PTTL). When assembling the battery, the operation is as follows: assemble in the order of negative electrode shell, spring sheet, stainless steel sheet (SS), negative electrode (lithium foil), TTL precursor solution (15μL), PAN, TTL precursor solution (15μL), positive electrode, and positive electrode shell, and put the assembled battery into an oven (80℃, 4h) for thermal initiation of polymerization.

[0051] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A polycarbonate gel electrolyte, characterized in that: The electrospun PAN porous fiber membrane is used as the substrate, and after being soaked in a mixture of polymerizable carbonate monomer, multifunctional thiol monomer, thermal initiator and electrolyte, it is prepared by thermal initiation polymerization. The general structural formula of the polymerizable carbonate monomer is as follows: The functionality of the multifunctional mercapto monomer is greater than 2.

2. The polycarbonate gel electrolyte according to claim 1, characterized in that: The electrostatically spun PAN porous fiber membrane has a fiber diameter of 350-450 nm and a thickness of 20-200 μm.

3. The polycarbonate gel electrolyte according to claim 1, characterized in that: The thermal initiator is azobisisobutyronitrile.

4. The polycarbonate gel electrolyte according to claim 1, characterized in that: The electrolyte is one of 1M LiDFOB in EC / DMC=1 / 1Vol%, 1M LiTFSI in EC / DMC=1 / 1Vol%, 1M LiTFSI in EC / DEC / DMC=1 / 1 / 1Vol%, and 1M LiDFOB in EC / DEC / DMC=1 / 1 / 1Vol%.

5. The polycarbonate gel electrolyte according to claim 1, characterized in that: In the mixed solution, the molar ratio of the polymerizable carbonate monomer to the mercapto group-containing monomer is 1:1; the mass ratio of the electrolyte to the total mass of the polymerizable carbonate monomer and the mercapto group-containing monomer is 1:1; and the amount of the thermal initiator used is 1% of the mass of the polymerizable carbonate monomer.

6. The polycarbonate gel electrolyte according to claim 1, characterized in that: The thermally initiated polymerization is carried out in an environment of 75-85° C. for 3-5 hours.

7. Use of the polycarbonate gel electrolyte according to any one of claims 1 to 6 in a lithium metal battery.

8. Use of the polycarbonate gel electrolyte in a battery according to claim 7, characterized in that: The electrospun PAN porous fiber membrane soaked in the mixed solution is assembled with other components of the battery, and then in-situ thermal polymerization is carried out; the other components of the battery include a negative electrode shell, a spring sheet, a stainless steel sheet, a negative electrode, a positive electrode and a positive electrode shell, and the assembly order is negative electrode shell, spring sheet, stainless steel sheet, negative electrode, electrospun PAN porous fiber membrane soaked in the mixed solution, positive electrode and positive electrode shell.